High rate of dyspareunia and probable vulvodynia in Ehlers–Danlos syndromes and hypermobility spectrum disorders: An online survey. Issue 4 (7th November 2021) - Glayzer, Jennifer E.; McFarlin, Barbara L.; Castori, Marco; Suarez, Marie L.; Meinel, Monya C.; Kobak, William H.; Steffen, Alana D.; Schlaeger, Judith M.
Abstract: Vulvodynia is debilitating vulvar pain accompanied by dyspareunia (pain with sexual intercourse). Ehlers–Danlos syndromes (EDS) and hypermobility spectrum disorders (HSD) may represent a predisposing factor for vulvodynia given a high rate of dyspareunia in these conditions. We conducted an online survey of women with EDS or HSD to assess rates of dyspareunia and estimate rates of vulvodynia, report rates of comorbid conditions common to EDS or HSD and vulvodynia, and examine rates of conditions contributing to dyspareunia in women with EDS or HSD. Women with EDS or HSD ( N  = 1, 146) recruited via social media were 38.2 ± 11.5 years old, primarily White (94.4%), and resided in the United States (78.5%). 63.7% of participants reported dyspareunia and 50% screened positive for vulvodynia. The rate of comorbid conditions common to EDS or HSD and vulvodynia were: irritable bowel syndrome, 6.5%; fibromyalgia, 40.0%; temporomandibular joint dysfunction, 56.4%; migraine, 6.7%; interstitial cystitis, 1.7%; and mast cell activation syndrome, 10.2%. Participants reporting dyspareunia also reported ovarian cysts, fibroids, or abdominal or pelvic scars, 47.5%; endometriosis, 26.5%; and genital lacerations, 19.3%. Women with EDS or HSD may have a higher rate of vulvodynia (50.0%) than women in the U.S. population at large (8%) and should be assessed for dyspareunia and vulvodynia.